2011
DOI: 10.1097/wnn.0b013e3182313020
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance in Asymptomatic Patients With Advanced Carotid Disease

Abstract: : The MoCA successfully identified reduced cognitive status in patients with ICAs/o. The MoCA subtest scores revealed a pattern of cognitive impairment similar to that documented in other studies using more extensive neuropsychological tests. MoCA could be used as part of the clinical evaluation of patients with ICAs/o.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 44 publications
4
35
0
Order By: Relevance
“…Subtest differences could be seen even among those whose Mini Mental Status Examination (MMSE) scores were within normal limits. Second, performance on the visuospatial/executive subtest is worse among patients with occlusion/stenosis of the ICA than among patients with vascular risk factors whose ICA is normal, and worse still for ICA patients with more than 2 vascular risk factors [35,36]. In contrast, 1 study found no group differences on any subtest scores when comparing patients with mild-to-moderate vascular dementia with a group of patients with mild-to-moderate Alzheimer's disease who were carefully matched for age, gender, education and total MMSE score [44].…”
Section: Content Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Subtest differences could be seen even among those whose Mini Mental Status Examination (MMSE) scores were within normal limits. Second, performance on the visuospatial/executive subtest is worse among patients with occlusion/stenosis of the ICA than among patients with vascular risk factors whose ICA is normal, and worse still for ICA patients with more than 2 vascular risk factors [35,36]. In contrast, 1 study found no group differences on any subtest scores when comparing patients with mild-to-moderate vascular dementia with a group of patients with mild-to-moderate Alzheimer's disease who were carefully matched for age, gender, education and total MMSE score [44].…”
Section: Content Evidencementioning
confidence: 99%
“…A multitude of studies comparing the MoCA to the MMSE as a cognitive screening tool were unanimous in concluding the following: (1) MoCA scores are normally distributed, whereas MMSE scores show ceiling effects, (2) the prevalence of cognitive impairment among patients with cerebrovascular disease using the originally published cut-off scores is greater when assessed using the MoCA than when using the MMSE and (3) while a substantial number of those who pass the MMSE fail the MoCA, the converse is rarely true. This has been demonstrated in clinical samples composed of patients with any stroke [18,22], any stroke or TIA [12,14,15,20,21,29,34], small-vessel disease or silent cerebral infarct [25,33], SAH [39,40] and stenosis or occlusion of the ICA [35,36]. …”
Section: Consequencesmentioning
confidence: 99%
“…Accumulating evidence showed that patients with severe carotid artery stenosis are correlated with VCI in memory (Inzitari et al., 2000; Popovic et al., 2011; Sztriha, Nemeth, Sefcsik, & Vecsei, 2009). Patients with high‐grade carotid artery disease showed lower scores on cognitive function tests than normal controls (Sander et al., 2010; Silvestrini et al., 2011; Zhong et al., 2011, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now well recognized that progressive decline in cognitive functioning may result from cerebrovascular disease, even in the absence of a clinically detectable precipitating event (Jokinen et al, 2009). In 2006, the National Institute of Neurological Disorders and the Stroke-Canadian Stroke Network recommended the Montreal Cognitive Assessment (MoCA) test, or some of its subtests, as an optimal brief protocol for the assessment of vascular cognitive impairment (Hachinski et al, 2006, Popovic, Lovrencic-Huzjan, & Demarin, 2009Popovic et al, 2011). The MoCA compares equally or favorably to the mini-mental state examination (MMSE) in terms of sensitivity to cognitive impairment and sensitivity to change, over time (Koski, 2013).…”
Section: Introductionmentioning
confidence: 99%